ExplorerTree: A Focus+Context Exploration Approach for 2D Embeddings - Marcílio-Jr, Wilson E. [UNESP]; Eler, Danilo M. [UNESP]; Paulovich, Fernando V.; Rodrigues-Jr, José F.; Artero, Almir O. [UNESP] (Elsevier, 2021)
In exploratory tasks involving high-dimensional datasets, dimensionality reduction (DR) techniques help analysts to discover patterns and other useful information. Although scatter plot representations of DR results allow for cluster identification and similarity analysis, such a visual metaphor presents problems when the number of instances of the dataset increases, resulting in cluttered visualizations. In this work, we propose a scatter plot-based multilevel approach to display DR results and address clutter-related problems when visualizing large datasets, together with the definition of a methodology to use focus+context interaction on non-hierarchical embeddings. The proposed technique, called ExplorerTree, uses a sampling selection technique on scatter plots to reduce visual clutter and guide users through exploratory tasks. We demonstrate ExplorerTree's effectiveness through a use case, where we visually explore activation images of the convolutional layers of a neural network. Finally, we also conducted a user experiment to evaluate ExplorerTree's ability to convey embedding structures using different sampling strategies.
Keywords: Dimensionality reduction; Focus+context; Scatter-plot; Visualization